Emotional self-regulation and personality in the light of Thomas Aquinas’s philosophical anthropology - Rojas-Saffie, Juan Pablo; García-Matte, Nicolás (Frontiers in Psychology, 2024)
This article aims to thoroughly understand the concept of emotional self-regulation (ESR) and its relationship with personality. Through an interdisciplinary dialogue between psychology and philosophy —specifically, the anthropology of Thomas Aquinas— three realities are proposed that could be considered as ESR. The conceptual relationship between ESR —understood as operation, faculty and habit— and personality is examined, specifically using the Five-Factor Model and the virtues model. Key findings include the need for consensus on a precise definition of ESR, the central role of reason as a faculty capable of ruling over emotions, the relevance of the distinction between ESR and self-control, and the understanding of ESR as a set of habits that include aspects of prudence, temperance and fortitude. Interdisciplinary dialogue seems to be a valuable intellectual approach to the advancement of the field of psychology.